2022
DOI: 10.1021/acs.jpcc.2c02528
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Electron Transfer from CdS Nanorods to the MoFe Protein of Nitrogenase

Abstract: Combining the remarkable catalytic properties of redox enzymes with highly tunable light absorbing properties of semiconductor nanocrystals enables the light-driven catalysis of complex, multielectron redox reactions. This Article focuses on systems that combine CdS nanorods (NRs) with the MoFe protein of nitrogenase to drive photochemical N2 reduction. We used transient absorption spectroscopy (TAS) to examine the kinetics of electron transfer (ET) from CdS NRs to the MoFe protein. For CdS NRs with dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 76 publications
(211 reference statements)
1
10
0
Order By: Relevance
“…Utterback et al studied charge transfer from CdS nanorods to Fe–Fe hydrogenase and measured electron transfer times in the 10s of ns . Recently, Ruzicka et al investigated the dynamics of CdS nanorods (NRs) with the MoFe protein of nitrogenase and also measured a few ns charge transfer time …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Utterback et al studied charge transfer from CdS nanorods to Fe–Fe hydrogenase and measured electron transfer times in the 10s of ns . Recently, Ruzicka et al investigated the dynamics of CdS nanorods (NRs) with the MoFe protein of nitrogenase and also measured a few ns charge transfer time …”
mentioning
confidence: 99%
“…21 Recently, Ruzicka et al investigated the dynamics of CdS nanorods (NRs) with the MoFe protein of nitrogenase and also measured a few ns charge transfer time. 22 However, these studies focused on CdS nanoparticles which have been considered toxic to many living organisms and therefore should only stay on the outside of the living cell. In that case, the charge transfer from the inorganic nanoparticle to the organism must go through the cell membrane, and that process hinders the charge-transfer rate, resulting in the 10s of ns charge transfer times.…”
mentioning
confidence: 99%
“…We have employed MST to study the nature of these interactions and have demonstrated that their apparent strength is on the same order for the Fe protein and QDs, but the two exhibit different polarity in cooperative behavior indicating there are differences in the nature of the binding interactions and perhaps different sites for binding. Previous modeling has indicated that the most likely sites for binding for QDs having negatively charged 3-MPA ligands are two positively charged surface patches on the MoFe protein that are of sufficient/appropriate size and charge to support substantial interaction . The observation that NaCl has a significant impact on the strength of binding supports the model that electrostatic interactions are dominant in complex formation.…”
mentioning
confidence: 84%
“…In addition, specific activities of the MoFe protein (nmol product/mg MoFe protein/min) for protons and nonphysiological substrates are low compared to those observed with Fe protein/MgATP/DT as the electron delivering system. MoFe protein complexes with Ru-photosensitizers were also reported to be unstable and to exhibit low quantum yields (QY ≤ 1%) of product formation. ,, More recently, our team has shown that biohybrid systems consisting of CdS NCs and MoFe protein (Figure ) can catalyze the reduction of N 2 to NH 3 upon illumination. , Complexation of MoFe protein with CdS NCs with surfaces functionalized with 3-mercapto­propionate (3-MPA) has enabled a suite of significant mechanistic studies on nitrogen reduction catalysis. Presumably catalysis relies on the association of the 3-MPA capped CdS NCs and the MoFe protein, which is a prerequisite for the injection of photoexcited electrons from the NC to the MoFe protein, and we expect these interactions to be primarily electrostatic in nature . Despite its critical importance, tools for characterizing NC-enzyme binding are lacking.…”
mentioning
confidence: 99%
“…In earlier work, we demonstrated that MoFe protein can be reduced by photochemical electron delivery from photoexcited CdS nanocrystals (Figure ). The physical coupling of nanocrystal materials and MoFe protein enables electron delivery under illumination at different temperatures. , Illumination of reactions in the frozen state (∼233 K) has been used to photoaccumulate and trap P cluster or FeMo-co cluster intermediates in the absence of catalytic turnover. , Therefore, this approach might be useful for generating and testing the stability of catalytic intermediates in the absence of turnover and H 2 production. Herein, CdS quantum dot (QD)-MoFe protein biohybrids were prepared and illuminated in reactions at 233 K under 1 atm of N 2 , followed by cryo-annealing in the dark at 236 K (see Supporting Information for details).…”
mentioning
confidence: 99%